The politics of the veil - Scott, Joan Wallach (New Jersey Princeton University Press, 2007)
"In 2004, the French government instituted a ban on the wearing of "conspicuous signs" of religious affiliation in public schools. Though the ban applies to everyone, it is aimed at Muslim girls wearing headscarves. Proponents of the law insist it upholds France's values of secular liberalism and regards the headscarf as symbolic of Islam's resistance to modernity. The Politics of the Veil is an explosive refutation of this view, one that bears important implications for us all. Joan Wallach Scott, the renowned pioneer of gender studies, argues that the law is symptomatic of France's failure to integrate its former colonial subjects as full citizens. She examines the long history of racism behind the law as well as the ideological barriers thrown up against Muslim assimilation. She emphasizes the conflicting approaches to sexuality that lie at the heart of the debate--how French supporters of the ban view sexual openness as the standard for normalcy, emancipation, and individuality, and the sexual modesty implicit in the headscarf as proof that Muslims can never become fully French. Scott maintains that the law, far from reconciling religious and ethnic differences, only exacerbates them. She shows how the insistence on homogeneity is no longer feasible for France--or the West in general--and how it creates the very "clash of civilizations" said to be at the root of these tensions. The Politics of the Veil calls for a new vision of community where common ground is found amid our differences, and where the embracing of diversity--not its suppression--is recognized as the best path to social harmony."
The headscarf controversies -- Racism -- Secularism -- Individualism -- Sexuality.
Includes bibliographical references (p. [185]-197) and index.
Donated by Atty. Mehol K. Sadain, UP Institute of Islamic Studies, 2018.
Keywords: Islamophobia -- France; Racism -- France; Muslims -- France; Hijab (Islamic clothing) -- Law and legislation -- France; Muslims -- Cultural assimilation -- France; Secularism -- France; Culture conflict -- France